하이브리드 입자-격자 방법에서의 압력장 계산 - 이승재(Seung-Jae Lee); 서정천(Jung-Chun Suh) (大韓造船學會 論文集, 2014)
A hybrid particle-mesh method based on the vorticity-velocity formulation for solving the incompressible Navier-Stokes equations is a combination of the Vortex-In-Cell(VIC) method for convection and the penalization method for diffusion. The key feature of the numerical methods is to determine velocity and vorticity fields around a solid body on a temporary grid, and then the time evolution of the flow is computed by tracing the convection of each vortex element using the Lagrangian approach. Assuming that the vorticity and velocity fields are to be computed in time domain analysis, pressure fields are estimated through a complete set of solutions at present time step. It is possible to obtain vorticity and velocity fields prior to any pressure calculation since the pressure term is eliminated in the vorticity-velocity formulation. Therefore, pressure field is explicitly treated by solving a suitable Poisson equation. In this paper, we propose a simple way to numerically implement the vorticity-velocity-pressure formulation including a penalty term. For validation of the proposed numerical scheme, we illustrate the early development of viscous flows around an impulsive started circular cylinder for Reynolds number of 9500.